Normans and Other Franks in 11th Century Byzantium: the Careers of the Adventurers before the Rule of Alexius I Comnenus - Wierzbiński, Szymon (Studia Ceranea, 2014)
The paper examines the Frankish presence in Byzantium during 11th century. It was stressed that the mentioned period was the time of a great influx of westerners to the East. At first, most of them visited Constantinople as pilgrims during return journey from the Holy Land. The author points out that the term Franks (Frankoi) was basically attributed to the Eastern Franks/Germans, while in the course of time the Byzantines started to use it to identify rather Western Franks (i.e. French, Normans, Burgundians etc.). The author studies the circumstances in which the new mercenaries and adventurers meet the Empire, trying to define the reason of their success. Another issue investigated in the text is the extent to which Franks got promoted within the social hierarchy in Byzantium during the 11th century. Finally, the author argues that before the presence of great families such as Petraliphai, Raoul or Rogerioi there was at least one house of Frankish descent, which was raised significantly earlier and whose founder was Herve Frankopoulos.